Turkish Astragalus Species: Botanical Aspects, Secondary Metabolites, and Biotransformation - Ekiz Dinçman, Güner; Aytaç, Zeki; Çalış, İhsan (Planta Medica, 2024)
Astragalus is a widespread genus comprising approximately 3500 species, both annual and perennial, found across Asia, Europe, Africa, and the Americas. In Turkey, it is represented by 63 sections and 485 taxa with a high endemism ratio (51%). In traditional medicine, the roots of various Astragalus species represent very old and well-known drugs used for antiperspirant, diuretic, and tonic purposes, as well as for the treatment of nephritis, diabetes, leukemia, and uterine cancer. The genus Astragalus is the richest source of cycloartane-type compounds, which display a diverse range of bioactivities, such as wound healing, immunomodulatory, antitumor, hepatoprotective, antimutagenic, antiviral, and antiprotozoal activities. Moreover, cycloastragenol, the main sapogenol of many cycloartane-type glycosides found in the Astragalus genus, has gained attention as a potent telomerase activator over the past decade. The preparation of cycloastragenol derivatives could be significant in the near future due to their unique bioactivity. This review covers the botanical aspects of Astragalus L., as well as the phytochemical and biological activity studies conducted on Turkish Astragalus species, with a special focus on cycloartenols. It contains 36 articles reporting the phytochemistry of 29 Astragalus species and 111 new compounds, including 104 triterpene saponins. In addition to the phytochemical studies, this review summarizes the biotransformation studies on Astragalus cycloartanes via endophytic fungi isolated from the tissues of Astragalus species.
Keywords: Astragalus; Leguminosae; botany; phytochemistry; cycloartenols; biological activity; biotransformation